Răspuns :
=[1+(2-x)/(x+1)]:[(x-1)/(4x²+2x+2x+1-x²-2x-2x-4)=
=[(x+1)+(2-x)]/(x+1):[(x-1)/(3x²-3)]=
=[3/(x+1)]:[(x-1)/3(x-1)(x+1)] simplificam in paranteza mare cu x-1=
=3/(x+1):1/3(x+1)=
=3/(x+1)·3(x+1)/1=simplificam cu x+1 si cu 3=
=3·3=9
=[(x+1)+(2-x)]/(x+1):[(x-1)/(3x²-3)]=
=[3/(x+1)]:[(x-1)/3(x-1)(x+1)] simplificam in paranteza mare cu x-1=
=3/(x+1):1/3(x+1)=
=3/(x+1)·3(x+1)/1=simplificam cu x+1 si cu 3=
=3·3=9
E(x)=(1+[tex] \frac{2-x}{x+1} [/tex]):[tex] \frac{x-1}{ (2x+1)^{2} - (x+2)^{2} } [/tex]=
=[tex] \frac{x+1+2-x}{x+1} [/tex] * [tex] \frac{ (2x+1)^{2} - (x+2)^{2}{x-1} } [/tex]=
=[tex] \frac{3}{x+1} [/tex] * [tex] \frac{4 x^{2} +4x+1-( x^{2} +4x+4)}{x-1} [/tex]=
=[tex] \frac{3}{x+1} [/tex] * [tex] \frac{3 x^{2} -3}{x-1} [/tex]=
=[tex] \frac{3}{x+1} [/tex] * [tex] \frac{3( x^{2} -1)}{x-1} [/tex]=
=[tex] \frac{3}{x+1} [/tex] * [tex] \frac{3(x -1)(x+1)}{x-1} [/tex]=
=9
=[tex] \frac{x+1+2-x}{x+1} [/tex] * [tex] \frac{ (2x+1)^{2} - (x+2)^{2}{x-1} } [/tex]=
=[tex] \frac{3}{x+1} [/tex] * [tex] \frac{4 x^{2} +4x+1-( x^{2} +4x+4)}{x-1} [/tex]=
=[tex] \frac{3}{x+1} [/tex] * [tex] \frac{3 x^{2} -3}{x-1} [/tex]=
=[tex] \frac{3}{x+1} [/tex] * [tex] \frac{3( x^{2} -1)}{x-1} [/tex]=
=[tex] \frac{3}{x+1} [/tex] * [tex] \frac{3(x -1)(x+1)}{x-1} [/tex]=
=9